Effect of 9.3 μm CO2 and 2.94 μm Er:YAG Laser vs. Bur Preparations on Marginal Adaptation in Enamel and Dentin of Mixed Class V Cavities Restored With Different Restorative Systems - Anton y Otero, Clara Isabel; Di Bella, Enrico; Krejci, Ivo; Bortolotto, Tissiana (Frontiers in Dental Medicine, 2021)
This study aimed to compare the efficacy of laser versus bur-prepared mixed class V cavities restored by different one component self-etching universal adhesives. Seventy two caries-free human molars were attributed to 9 experimental groups and cavities were prepared using two different lasers with different parameters: A handpiece -integrated Er:YAG laser @ 4.5 W, 300 mJ, and 0.75 W, 50 mJ with 15 Hz (LiteTouch, Light Instruments, Israel) and a novel CO2 laser @ 12.95 W, 19.3 mJ and 4.1 W, 6.11 mJ with 671 Hz (Solea 9.3 µm, Convergent Dental, USA). Cavities prepared with conventional diamond burs (Intensiv, Switzerland) in a red contra angle at high speed under maximal water cooling served as control. Cavities were prepared under simulation of dentinal fluid and restored using 3 different self-etching universal adhesives in combination with three nanohybrid composites, applied in two layers: Scotchbond Universal with Filtek Supreme XTE (3M, USA); G-Premio BOND with Essentia Universal (GC, Japan) and OptiBond Universal with Harmonize Universal (Kerr, USA). After restorations’ polishing and simultaneous thermal (5-50 °C, 2 minutes each) and mechanical loading (max. 49 N; 200000 cycles) restoration margins were examined under SEM at 200x magnification. Percentages of continuous margins were quantified before and after the fatigue test and statistically compared (2-way ANOVA with Fisher’s LSD post-hoc-test). Significant differences were found in almost all groups between the results before and after the fatigue test, as well as between the different preparation tools and restorative materials (p < 0.05). The marginal quality of bur-prepared restorations was not significantly different from Er:YAG laser-prepared restorations with ScotchBond Universal adhesive/Filtek Supreme XTE. Quality of marginal adaptation after laser-preparation can be, depending on the type of laser and material used, as effective as bur-preparation.